2020
DOI: 10.21873/anticanres.14172
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 and MMSET Were Identified as Potentially Useful Therapeutic Targets in Metaplastic Breast Carcinoma

Abstract: Background/Aim: Metaplastic breast carcinoma (MBC) is a rare malignancy, which is often triple-negative for the hormone receptors and human epidermal growth factor receptor 2, and thus, does not benefit from targeted therapy. In this study, we examined the expression of methylation and demethylation enzymes by immunostaining MBC and the adjacent normal tissues or triple-negative ductal carcinoma (TNDC), and identified alterations that may be used as therapeutic targets. Materials and Methods: We retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…NSD1 is associated with several cancers, including acute myeloid leukemia and lung cancer. , In comparison, NSD2 is associated with a broad spectrum of malignancies due to gene translocation, overexpression, and mutation . Moreover, several reports have suggested that NSD2 is overexpressed in various cancers including multiple myeloma, skin, lung, bladder, prostate, and brain cancers. , Furthermore, Nakayama et al also identified NSD2 as a potential target in metaplastic breast cancer. NSD3 promotes cell-cycle progression and proliferation by activating signaling pathways and plays essential roles in the development of breast and small-cell lung cancers and pancreatic adenocarcinoma. , In addition, Kang et al reported that the knockdown of NSD3 expression suppressed proliferation of liver, bladder, and lung cancer cell lines by inducing G 2 /M cell cycle arrest.…”
Section: Introductionmentioning
confidence: 99%
“…NSD1 is associated with several cancers, including acute myeloid leukemia and lung cancer. , In comparison, NSD2 is associated with a broad spectrum of malignancies due to gene translocation, overexpression, and mutation . Moreover, several reports have suggested that NSD2 is overexpressed in various cancers including multiple myeloma, skin, lung, bladder, prostate, and brain cancers. , Furthermore, Nakayama et al also identified NSD2 as a potential target in metaplastic breast cancer. NSD3 promotes cell-cycle progression and proliferation by activating signaling pathways and plays essential roles in the development of breast and small-cell lung cancers and pancreatic adenocarcinoma. , In addition, Kang et al reported that the knockdown of NSD3 expression suppressed proliferation of liver, bladder, and lung cancer cell lines by inducing G 2 /M cell cycle arrest.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, in neoplastic cells, it activates transcription and stimulates proliferation. EZH2 alterations, both protein overexpression and mutations, were described in both solid tumors, i.e., breast (14)(15)(16)(17)(18), hepatocellular (19,20), gastric (21), urothelial (22,23), prostate carcinomas (24,25), melanoma (26,27) and in non-Hodgkin's lymphomas (NHL) i.e., diffuse large B-cell lymphoma (DLBCL), FL, Burkitt lymphoma and other small cell and aggressive B-cell NHL (28,29). The inferior impact of EZH2 overexpression on overall survival has been outlined independently (30).…”
mentioning
confidence: 99%